2005
DOI: 10.1021/ma0508451
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Solid State Polymerization ofp-Ethynylbenzoic Acid

Abstract: While p-ethynylbenzoic acid (EBA) has been suggested to be reactive in the solid state, the structure-reactivity relationships and the nature of the product(s) have remained unknown. Crystallized from toluene, EBA is a monoclinic crystal, space group P2 1/n, a ) 3.8684( 4), b ) 6.2329(4), c ) 30.190(3) Å; β ) 90.281(8)°; V ) 727.90 Å 3 . The crystal structure contains linear chains and short intermolecular contacts between acetylene moieties, which provide a structural basis for initiation of topochemical reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 70 publications
1
6
0
Order By: Relevance
“…Crystalline PEBA reveals thermal and UV-induced reactivity. In the solid state, the photopolymerization reaction is topochemically promoted by the proximity of adjacent molecules within the crystal lattice . We therefore assumed that by taking advantage of the collinear displacement of neighboring alkynes on the HOPG surface, a topochemical homocoupling could be promoted photochemically.…”
Section: Resultssupporting
confidence: 89%
“…Crystalline PEBA reveals thermal and UV-induced reactivity. In the solid state, the photopolymerization reaction is topochemically promoted by the proximity of adjacent molecules within the crystal lattice . We therefore assumed that by taking advantage of the collinear displacement of neighboring alkynes on the HOPG surface, a topochemical homocoupling could be promoted photochemically.…”
Section: Resultssupporting
confidence: 89%
“…However, Foxmann et al reported the crystalline-state controlled polymerization of a substituted phenylacetylene with high reactivity. 94 In the crystalline state, the molecular packing of the acetylene groups is in parallel arrangement, and the orientation is suitable for the resultant poly(acetylene) structures. However, the distance between the monomers is longer than that of the expected repeating distances.…”
Section: Crystalline-state Polymerization Of Other Polymerizable Groupsmentioning
confidence: 99%
“…1‐(3‐Dimethylaminopropyl)−3‐ethylcarbodiimide hydrochloride (TCI, 98%), 4‐dimethylaminopyridine (DMAP; TCI, 98%), TFA (Wako, 98%), ethylaluminum dichloride (EtAlCl 2 ; Wako, 1.0 M in n ‐hexane), and 2‐hydoxyethyl vinyl ether (Maruzen Petrochemical, 99.9%) were used as received. p ‐Ethynylbenzoic acid was prepared according to a literature with some modifications. Isobutyl vinyl ether (IBVE; Aldrich, 99%) was dried overnight over KOH pellets, and distilled twice over CaH 2 .…”
Section: Methodsmentioning
confidence: 99%